MANAJEMEN PENDIDIKAN QIRA’AT SAB’AH DI PONDOK TAHFIDH YANBU’UL QUR’AN REMAJA (PTYQR) KUDUS - Hariyanto, Ahmad (Jurnal Al Burhan, 2023)
Pondok Tahfidh Yanbu'ul Qur'an Remaja Bejen Kudus City is one of the institutions that provides formal academic-based tahfidh education. This article will examine specifically the management of qira'at sab'ah education at Pondok Tahfidh Yanbu'ul Qur'an Remaja Bejen, Kudus City because in the world of education, there are not many or even very few educational institutions that teach qira'at sab'ah in learning program. On the other hand, the relationship between qira'at sab'ah and Yanbu'ul Qur'an has an iconic history from its founder, KH. Muhammad Arwani is the only student from KH. Munawwir was the master of qira'at sab'ah at that time and added his work in the form of the book Faidh al-Barakât fî sab' al-Qirâ'ât as a textbook used in education. With a phenomenology approach by taking case study objects, both through direct (participant) and indirect observation. The results obtained by the research are the background to the birth of the concept of qira'at sab'ah education at the Pondok Tahfidh Yanbu'ul Qur'an Remaja which is typical, namely mudarasah, the system built in qira'at sab'ah learning activities is talaqqî and musyâfahah, it has a systematic three stages of learning, namely ifrâd, jama' sughrâ and jama' kubro, the conditions that apply to students who take part in this activity are none other than khatimin students who have strong potential, enthusiasm and attention, and the resulting product is four students who are khatam qira' at sab'ah binnadzar.